Resíduos e espaço urbano: o metabolismo dos resíduos sólidos urbanos na Região Metropolitana de Belo Horizonte - Beatrice Correa de Oliveira (2020)
This dissertation studies the material and representative aspects of the municipal solid waste (MSW) metabolism in the Metropolitan Region of Belo Horizonte (MRBH). Based on the understanding that the MSW is a geographic, social, historical and spatially constructed object, therefore, relevant to the comprehension of the relationship between man and space, this work sought, through bibliographic research, to analyze the different understandings about solid waste and make a historic recovery on the solid waste management guidelines in cities. The theoretical-methodological approach of urban political ecology provided the conceptual keys for the analysis and helped to understand the contours of the society-nature dynamics within the metropolises. The work turned to the case study of MRBH, based on the historical survey of the policies, plans and dynamics of the metropolitan region in relation to MSW, and on the identification of paradigms, actors and regulations related to the MSW management in the Metropolitan Region of BH. Subsequently, the analysis of secondary data brought information on MSW flows and paths in the cities of the studied metropolitan region. Interviews with agents linked to the MSW flux clarified the current management framework in the metropolis. Three moments of institutional initiatives to work on solid waste management in a metropolitan way were identified: a first attempt in the 1980s, proposed by Plambel. Another moment identified was the elaboration of the Integrated Development Plan of the MRBH published in 2011; and as of 2011, a third moment, marked by the implementation of a Public Private Partnership, with a consortium of companies responsible for the transshipment and final disposal of the MRBH’s garbage. The study identified that the option for a PPP is also fraught with political assumptions and choices, as political ecology allows to affirm. These choices were not supported by the change of government and the context of the state’s fiscal crisis, so it was considered that the third moment ended in 2014. The study concluded that different representations in relation to MSW coexist in the MRBH, while the metropolitan management proposal for MSW has weakened in recent years. However, public initiatives to metropolize the management of MSW have been limited to the problem of the materiality of waste in the metropolis and the urgency of an adequate final destination flow; this still proves to be the biggest challenge for municipalities, and it is an opportunity for the inclusion of waste pickers.